Estudio de prefactibilidad para la instalación de una empresa de servicios de partidos de fútbol 7 con soporte de TI - Hidalgo Torres, Jose Felix Isaac (2020)
The following project aims to prove the feasibility of creating a soccer-related company, of what is called Football 7-a-side games, using IT (Information Technology) support in Metropolitan Lima, aimed to young adults, people between 21 and 35 years old, who usually don’t realize as much physical activity as they would want, because of numerous factors. This service’s purpose is precisely to satisfy that unattended demand while providing new alternatives in the market and a big factor such as IT in the game, which solves present problems such as lack of players to successfully organize a Football 7-a-side match, and the reserve of the pitch. In that aspect, the aggregated value this project brings is based on a high-quality sports center with IT support, consisted of an App and a Web page.